Vessel wall imaging in COVID-19 associated carotid atherothrombosis and stroke: a case report and literature review - Mohamad Syafeeq Faeez Md Noh; Abdul Hanif Khan Yusof Khan; Mohd Naqib Mohd Sabri; Mohd Fandi Al-Khafiz Kamis; Mohd Naim Mohd Yaakob; Ezamin Abdul Rahim; Ahmad Sobri Muda (Journal of Central Nervous System Disease, 2022)
COVID-19 associated neurological syndromes, including acute ischemic stroke, pose a challenge to treating physicians. The role of MRI in aiding diagnosis and further management is indispensable. The advent of new MRI sequences such as vessel wall imaging (VWI) allows an avenue in which these patients could be better investigated and treated. We describe our experience in managing a patient with COVID-19 associated atherothrombosis and stroke, focusing on the VWI imaging findings.